Methodological Proposal for the Integration of a Document Management System Based on the General Archives Act and the Colombian Technical Standards 9001 Version 2015, 30300 Version 2013 and 30301 Version 2013 (2017)
Purpose: Document management represents an opportunity for organizations to streamline their processes and procedures because it helps eliminate redundant information, comply with legislation, ensure corporate memory, increase the performance of information technologies, and optimize response times. This research arises from the need of organizations to apply document management in an integrated manner between the requirements of Law 594/2000 - General Archives Act and the Colombian technical standard 9001 version 2015 [ntc-iso 9001:2015] on quality management, with the support of other specific references that facilitate document management, such as the Colombian technical standards 30300 and 30301 version 2013 [ntc-iso 30300:2013 and ntc-iso 30301:2013], maintaining the guidelines in the document management policy set out in international technical standard 15489 version 2016 [iso 15489:2016]. Description: A preponderantly qualitative, mixed approach study was conducted to establish the level of maturity of documentation in the mission and support processes of the National Institute of Legal Medicine and Forensic Sciences, using a diagnostic tool that allowed to determine the implementation status of the Colombian technical standard 9001 version 2015 [ntc-iso 9001:2015]. Also, another diagnostic tool was applied that provided the comprehensive status of the archive as set forth in the General Archives Act. Approach: It is striking that 40 % of the organization has the documentation identified and 60 % do not have standardized forms. Conclusions: Implementing the document management in accordance with quality management and the General Archives Act ensures improved productivity of processes, quick access to information, and compliance with regulations and the law, among other benefits.